2019
DOI: 10.1177/0023677219879170
|View full text |Cite
|
Sign up to set email alerts
|

Students’ acceptance of e-learning approaches in Laboratory Animal Science Training

Abstract: Different online courses and training programs in Laboratory Animal Science (LAS) have emerged across Europe in recent years. E-learning appears to be a promising solution to achieve flexibility in training while meeting the quality criteria of demanding programs in short training periods. However, little is known about how students perceive e-learning in this context, and there is also a lack of specific and valid instruments to measure this perception. Within an exploratory study framework, the e-learning pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
2
13
1
1
Order By: Relevance
“…The present study revealed the absence of significant associations between students' age with the total ElAM score and all its three facets (TQ, PU & FC). These results are in line with the results of Costa, et al [ 13 ]. On the other hand, this finding disagrees with the results of Teo, et al and Ngampornchai, et al from Thailand [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The present study revealed the absence of significant associations between students' age with the total ElAM score and all its three facets (TQ, PU & FC). These results are in line with the results of Costa, et al [ 13 ]. On the other hand, this finding disagrees with the results of Teo, et al and Ngampornchai, et al from Thailand [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, results from a recent meta-analysis, 2019, found that none of the sixteen studies included in their analysis reported that online learning was less effective than offline methods [ 18 ]. Similarly, the study of Costa, et al from Portugal revealed high levels of acceptance of e-learning [ 13 ]. The discrepancy between our research and the previous studies may also be due to the faculties' sudden closure during the pandemic with the complete shift to the full-time virtual learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also established the connection between academic measures and the stress rates of medical students as "severe stress" was apparent for the students who considered online learning "during pandemic" as a burden. On the contrary, other studies found that although the level of acceptance towards E-learning is still low, yet, more than 55% of the students found it to be useful and time-saving, 23 useful, and effective 24 Furthermore, our study recorded that online learning yielded "time management problems" for the majority of the students, whereas, other studies found that "online platforms" provide support for those who have time management problems 25 as well as technology can be used to shrink the total time students need to be in a class. 26 As a current finding, 41.2% of students who responded as "neutral" about "online learning content is difficult to understand" have exhibited stress.…”
Section: Discussionmentioning
confidence: 89%
“…In the context of teaching veterinary anatomy, a study showed that the method was well accepted and proved to be a useful and functional tool ( Costa, Costa, & Olsson, 2019 ).…”
Section: E-learningmentioning
confidence: 99%